Measuring the Meaning of Gender Equality Using Islamic and Christian Views - Azizah, Nur (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Gender equality is still an issue that attracts attention today, especially in Indonesia where people's understanding of this concept is still unclear. This article highlights the common misconception that gender equality leads to gender homogenization, when in fact the movement aims to eliminate discrimination against women in various aspects of life. This study aims to deepen understanding of gender equality from Islamic and Christian perspectives through qualitative research using the literature study method. The findings show that both Islam and Christianity recognize gender equality in their views, affirming that women have equal rights with men before God. The Koran and Islamic teachings emphasize the importance of fair treatment of women, while Christianity emphasizes human equality before God without distinction of gender.